Polycarbonate resin composition, molded article, and method for producing polycarbonate resin composition
Patent Information
- Application Number
- JP2023569007
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-12-24
AI Technical Summary
【0011】 本開示によれば、透明性を確保しつつ、親水性の粉塵汚れおよび疎水性の粉塵汚れのいずれも付着し難いポリカーボネート樹脂組成物および成形品を提供することができる。
Smart Images

Figure 0007646034000001 
Figure 0007646034000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polycarbonate resin composition, a molded article, and a method for producing a polycarbonate resin composition. [Background technology]
[0002] Polycarbonate resin has excellent transparency, mechanical properties, and heat resistance, but also has a high surface resistivity (10 14 Because of this, dust and other particles tend to adhere to the surface of the molded product, which may cause malfunctions and other problems when used in electrical equipment.
[0003] For this reason, antistatic polycarbonate resin compositions containing ionic liquids or conductive metal oxides with high antistatic performance have been investigated. However, adding a large amount of antistatic agent to improve antistatic performance can cause discoloration and a decrease in transparency, making it difficult to achieve both antistatic properties and transparency.
[0004] Methods for imparting antistatic properties while maintaining transparency include the addition of surfactants such as quaternary ammonium salts and sulfonates, conductive polymers such as polythiophene and polyaniline, and conductive metal oxides such as indium oxide and tin oxide. Methods for imparting antistatic properties to polycarbonate resin compositions have progressed from the addition of a single antistatic agent to the addition of multiple antistatic agents.
[0005] For example, Patent Document 1 (JP Patent No. 4870256) discloses metal salts selected from phosphonium sulfonate, potassium and sodium diphenylsulfone-3-sulfonic acid, and potassium and sodium perfluoroalkanesulfonic acid as antistatic agents. Patent Document 2 (JP Patent Publication 2009-107286 A) discloses phosphonium benzenesulfonate and phosphonium naphthylsulfonate as antistatic agents. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 4870256 [Patent Document 2] JP 2009-107286 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, although the above antistatic agent has a high total light transmittance and ensures transparency, it has a high surface resistivity (10 12 Ω / sq~10 13 In addition, since there is a high correlation between antistatic properties and dust adhesion, the effect was not sufficient against hydrophilic dust stains such as sand and dirt, and hydrophobic dust stains such as soot and oily smoke.
[0008] The present disclosure has been made to solve the above problems, and has an object to provide a polycarbonate resin composition and a molded article that are resistant to both hydrophilic and hydrophobic dust stains while ensuring transparency. [Means for solving the problem]
[0009] As a result of extensive research aimed at solving the above problems, the inventors have discovered that a synergistic effect can be achieved by combining a polycarbonate resin with a phosphonium salt-based ionic liquid and composite nanofibers, thereby achieving an anti-fouling effect that makes it difficult for both hydrophilic and hydrophobic dust stains to adhere while maintaining transparency. The present disclosure relates to the following polycarbonate resin compositions:
[0010] A polycarbonate resin composition comprising: 100 parts by weight of a polycarbonate resin (A); 0.5 to 5.0 parts by weight of a phosphonium salt-based ionic liquid (B); and 0.01 to 0.09 parts by weight of a composite nanofiber (C). Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a polycarbonate resin composition and a molded article that are resistant to both hydrophilic dust stains and hydrophobic dust stains while ensuring transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described.
[0013] Embodiment 1 <Polycarbonate resin composition> The polycarbonate resin composition of the present embodiment contains 100 parts by weight of a polycarbonate resin (A), 0.5 to 5.0 parts by weight of a phosphonium salt-based ionic liquid (B), and 0.01 to 0.09 parts by weight of a composite nanofiber (C).
[0014] In the polycarbonate resin composition of the present embodiment, by containing the polycarbonate resin (A), the phosphonium salt-based ionic liquid (B) and the composite nanofiber (C), the composition exhibits an antifouling effect that both hydrophilic dust stains and hydrophobic dust stains are difficult to adhere while ensuring transparency. The reasons for using each of the above components are explained below.
[0015] Since there is a high correlation between antistatic properties and dust adhesion, it has been common to add antistatic agents to reduce surface resistivity in order to improve dust adhesion. However, polycarbonate resin has a high surface resistivity (10 14 Therefore, even if an antistatic agent is added, the surface resistivity tends not to be reduced. Although polycarbonate resin has excellent transparency, mechanical properties, heat resistance, etc., the addition of an antistatic agent tends to cause clouding and deterioration of mechanical properties. In view of the above problems, the present inventors have investigated the addition of various antistatic agents to polycarbonate resin.
[0016] First, phosphonium salt-based ionic liquid was examined as an antistatic agent. Although the antistatic property was improved somewhat by adding a small amount of phosphonium salt-based ionic liquid, the surface resistivity was high (10 12 Ω / sq~10 13 In addition, when a large amount of phosphonium salt-based ionic liquid was added to reduce the surface resistivity, the transparency was reduced.
[0017] Next, the inventors investigated the addition of composite nanofibers as an auxiliary additive to the phosphonium salt-based ionic liquid. By adding the composite nanofibers, the phosphonium salt-based ionic liquid clings to the surface of the nanofibers and is aligned in the fiber direction, forming a conductive path, which reduces the surface resistivity, and a polycarbonate resin composition was obtained that is resistant to both hydrophilic and hydrophobic dust stains. Each component will be described in detail below.
[0018] (Polycarbonate resin (A)) The polycarbonate resin (A) contained in the polycarbonate resin composition of the present disclosure is not particularly limited, and various types can be used. For example, aromatic polycarbonates produced by a solution method (interfacial polycondensation method) or a melting method (ester exchange method) of a dihydric phenol and a carbonate precursor can be used. That is, those produced by reacting a dihydric phenol with phosgene by an interfacial polycondensation method, a dihydric phenol with diphenyl carbonate, or the like by an ester exchange method can be used.
[0019] As the dihydric phenol, various kinds can be mentioned, particularly 2,2-bis(4-hydroxyphenyl)propane [bisphenol A], bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 4,4'-dihydroxydiphenyl, bis(4-hydroxyphenyl)cycloalkane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)ketone, etc., or halogen-substituted products thereof. In addition, hydroquinone, resorcin, catechol, etc. can also be mentioned. These can be used alone or in combination of two or more kinds, but among these, bis(hydroxyphenyl)alkanes are preferred, and bisphenol A is more preferred.
[0020] The carbonate precursor may be a carbonyl halide, a carbonyl ester, a haloformate, or the like, and specifically, may be phosgene, a dihaloformate of a dihydric phenol, diphenyl carbonate, dimethyl carbonate, diethyl carbonate, or the like.
[0021] Polycarbonate resin (A) includes not only new materials but also polycarbonate resins recycled from used products. Any commercially available grade can be used, but optical grades with high transmittance are preferable. For example, Iupilon ML200, ML300, ML400, HL3003, HL3503 (Mitsubishi Engineering Plastics Co., Ltd.), SD Polyca 303-10, 303-30 (Sumika Polycarbonate Co., Ltd.), Lexan LS-1, LS-2, LS-3 (SABIC Innovative Plastics Japan LLC), Panlite L-1225Z, L-1225ZL (Teijin Co., Ltd.), Toughlon LC1500, LC1700 (Idemitsu Kosan Co., Ltd.), etc. can be used.
[0022] (Phosphonium salt-based ionic liquid (B)) The polycarbonate resin composition of the present disclosure contains a phosphonium salt-based ionic liquid (B). By containing the phosphonium salt-based ionic liquid (B), it is possible to improve antistatic properties (dust adhesion prevention properties).
[0023] Examples of the phosphonium salt-based ionic liquid (B) include tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide, tributyldodecylphosphonium bromide, tetrabutylphosphonium dodecylbenzenesulfonate, trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)imide, triethylpentylphosphonium bis(trifluoromethylsulfonyl)imide, triethyloctylphosphonium bis(trifluoromethylsulfonyl)imide, tri-n-butylmethylphosphonium bis(trifluoromethylsulfonyl)imide, tetrabutylphosphonium tetraphenylborate, etc. From the viewpoint of availability, it is preferable to use tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide, tributyldodecylphosphonium bromide, and tetrabutylphosphonium dodecylbenzenesulfonate.
[0024] Examples of tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imides that can be used include tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide (Fujifilm Wako Pure Chemical Industries, Ltd.) and IL-AP3 (Koei Chemical Industry Co., Ltd.); examples of tributyldodecylphosphonium bromides that can be used include tributyldodecylphosphonium bromide (Fujifilm Wako Pure Chemical Industries, Ltd.); and examples of tetrabutylphosphonium dodecylbenzenesulfonate that can be used include Elecut S-418 (Takemoto Oil Co., Ltd.).
[0025] The content of the phosphonium salt-based ionic liquid (B) in the present disclosure is 0.5 to 5.0 parts by weight, preferably 0.5 to 4.0 parts by weight, and more preferably 0.5 to 3.0 parts by weight, based on 100 parts by weight of the polycarbonate resin. When the content of the phosphonium salt-based ionic liquid (B) exceeds 5.0 parts by weight, not only the thermal stability at high temperatures is significantly reduced and coloring is easily caused, but also the mechanical properties may be significantly reduced. When the content of the phosphonium salt-based ionic liquid (B) is less than 0.5 parts by weight, the dust adhesion prevention property is reduced.
[0026] (Composite nanofiber (C)) The polycarbonate resin composition of the present disclosure contains a composite nanofiber (C). By containing the composite nanofiber (C), it is possible to improve antistatic properties (dust adhesion prevention properties).
[0027] The composite nanofiber (C) in the present disclosure refers to a fiber having a diameter on the order of nanometers, which is made by combining two or more kinds of metal oxides. Examples of metal oxides include silicon oxide (silica), aluminum oxide (alumina), zinc oxide, titanium oxide, calcium oxide, tin oxide, indium oxide, etc., and alumina and silica are preferred. In addition, the composite nanofiber (C) is preferably a nanofiber made by combining alumina and silica.
[0028] The composite nanofibers (C) preferably have an average fiber diameter of 100 nm or less. If the average fiber diameter of the composite nanofibers (C) exceeds 100 nm, Rayleigh scattering occurs, and transparency decreases. From the viewpoint of transparency, the average fiber diameter of the composite nanofibers (C) is more preferably 60 nm or less, and even more preferably 30 nm or less. The shape of the composite nanofibers (C) is not particularly limited, and may be, for example, fibrous, rod-like, tubular, hollow rod-like, core-shell fibrous, etc., with the core-shell fibrous being preferred.
[0029] The average fiber diameter of the composite nanofibers (C) is determined by taking electron microscope images of a sufficient number of composite nanofibers (C) (e.g., 100 or more) using an electron microscope (SEM, TEM, etc.), measuring the diameters of these composite nanofibers (C), and taking the arithmetic average.
[0030] In addition, the composite nanofiber (C) preferably has a refractive index at a wavelength of 589.3 nm of sodium D line close to 1.58, which is the refractive index of the polycarbonate resin (A) at a wavelength of 589.3 nm of sodium D line. If the refractive index of the composite nanofiber (C) is farther from 1.58, the difference between the refractive index of the polycarbonate resin (A) and the refractive index of the composite nanofiber (C) causes phenomena such as scattering and refraction, resulting in a decrease in transparency. From the viewpoint of transparency, the refractive index of the composite nanofiber (C) is preferably in the range of 1.40 to 2.00, more preferably in the range of 1.50 to 1.80, even more preferably in the range of 1.50 to 1.70, and even more preferably in the range of 1.58 to 1.60.
[0031] The refractive index can be adjusted by using a compound in which metal oxides having different refractive indexes are combined. For example, in the case of a core-shell fiber, a compound in which the core is made of alumina and the shell is made of silica can be used.
[0032] As the composite nanofiber (C), for example, R30SP-M2, R30SP-H1 (Admatechs Co., Ltd.), etc. can be used.
[0033] The content of the composite nanofiber (C) in the present disclosure is 0.01 to 0.09 parts by weight, preferably 0.02 to 0.08 parts by weight, and more preferably 0.02 to 0.07 parts by weight, based on 100 parts by weight of the polycarbonate resin. If the content of the composite nanofiber (C) exceeds 0.09 parts by weight, the haze increases and transparency may not be obtained. If the content of the composite nanofiber (C) is less than 0.01 parts by weight, the dust adhesion prevention property decreases.
[0034] (Additives) The polycarbonate resin composition of the present disclosure may contain additives such as a heat stabilizer, an ultraviolet absorber, and a light stabilizer, so long as the additives do not impede the object of the present disclosure.
[0035] [Heat stabilizer] The polycarbonate resin composition of the present disclosure may contain a heat stabilizer to improve thermal stability, since the inclusion of the ionic liquid (B) or the composite nanofiber (C) leads to hydrolysis, reduced thermal stability, and yellowing.
[0036] As the heat resistance stabilizer, it is preferable to use antioxidants such as hindered phenol-based, phosphorus-based and sulfur-based antioxidants, which may be used alone or in a mixture of two or more kinds.
[0037] The amount of the heat resistance stabilizer added in the present disclosure is not particularly limited, and the composition ratio when two or more types are mixed is also not particularly limited, but it is desirable to adjust each time depending on the required physical properties.
[0038] Examples of the hindered phenol-based antioxidants include known ones such as 2,6-di-tert-butyl-p-cresol, tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, stearyl β-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro(5,5)undecane, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-tert-butyl-4-hydroxybenzyl)benzene, and triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate]. Among these, from the viewpoint of heat resistance and stability, tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, stearyl β-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]-2,4,8,10-tetraoxaspiro(5,5)undecane are preferred.
[0039] Examples of phosphorus-based antioxidants include tris(2,4-di-tert-butylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, diphenyl monodecyl phosphite, pentaerythritol bis(2,6-di-tert-butyl-4-phenyl phosphite), 2,2'-methylene bis(4,6-di-tert-butylphenyl)-2-ethylhexyl phosphite, distearyl pentaerythritol diphosphite, tri(mono Examples of known phosphite include tris(2,4-di-tert-butylphenyl)phosphite, alkanol (C=12-16) 4,4'-isopropylidenediphenol triphenyl phosphite polycondensate, bis[2,4-di-tert-butyl-6-methylphenyl]ethyl phosphite, pentaerythritol bis(2,4-di-tert-butylphenyl phosphite), triallyl phosphite, and tetrakis(2,4-tert-butylphenyl)-4,4'-biphenyl diphosphonate. Among these, tris(2,4-di-tert-butylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, diphenyl monodecyl phosphite, pentaerythritol bis(2,6-di-tert-butyl-4-phenyl phosphite), and 2,2'-methylene bis(4,6-di-tert-butylphenyl)-2-ethylhexyl phosphite are preferred from the viewpoint of heat resistance stability.
[0040] Examples of sulfur-based antioxidants include known ones such as pentaerythritol tetrakis(3-laurylthiopropionate), dilauryl-3,3'-thiodipropionate, dioctadecyl-3,3'-thiodipropionate, etc. Among these, pentaerythritol tetrakis(3-laurylthiopropionate) is preferred from the viewpoint of heat resistance and stability.
[0041] The content of the heat stabilizer in the present disclosure is preferably 0.05 to 10 parts by weight, and more preferably 0.05 to 3.0 parts by weight, based on 100 parts by weight of the polycarbonate resin (A).
[0042] [Ultraviolet absorber] The polycarbonate resin composition of the present invention is often used in outdoor products and may contain an ultraviolet absorbing agent since it yellows due to ultraviolet light.
[0043] Examples of the ultraviolet absorber include known ones such as hydroxybis(dimethylbenzyl)phenylbenzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol], 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol), and 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine).
[0044] Among the above, from the viewpoint of weather resistance stability, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-tert-octylphenol], 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol), and 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine) are preferred. The above ultraviolet absorbers may be used alone or in a mixture of two or more kinds.
[0045] The amount of ultraviolet absorber added in the present disclosure is not particularly limited, and the composition ratio when two or more types are mixed is also not particularly limited, but it is desirable to adjust each time depending on the required physical properties.
[0046] The content of the ultraviolet absorber in the present disclosure is preferably 0.05 to 10 parts by weight, and more preferably 0.05 to 3.0 parts by weight, based on 100 parts by weight of the polycarbonate resin (A).
[0047] [Light stabilizer] The polycarbonate resin composition of the present disclosure is often used in outdoor products and may contain a light stabilizer since it is prone to yellowing due to ultraviolet light.
[0048] Examples of the light stabilizer include known ones such as tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, a mixed ester of 1,2,3,4-butanetetracarboxylic acid, 1,2,3,6,6-pentamethyl-4-piperidinol, and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane, and bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate.
[0049] Among the above, from the viewpoint of weather resistance stability, a mixed ester of 1,2,3,4-butanetetracarboxylic acid, 1,2,3,6,6-pentamethyl-4-piperidinol, and 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane is preferred. The above light stabilizers may be used alone or in a mixture of two or more kinds.
[0050] The amount of light stabilizer added in the present disclosure is not particularly limited, and the composition ratio when two or more types are mixed is also not particularly limited, but it is desirable to adjust each time depending on the required physical properties.
[0051] The content of the light stabilizer in the present disclosure is preferably 0.05 to 10 parts by weight, and more preferably 0.05 to 3.0 parts by weight, based on 100 parts by weight of the polycarbonate resin (A).
[0052] (Other additives) Other additives that can be used in the present disclosure include antistatic agents, plasticizers, release agents, flame retardants, flame retardant auxiliaries, dyes, pigments, and the like, so long as they do not impede the object of the present disclosure.
[0053] The antistatic agent can be arbitrarily selected from known ionic liquids such as phosphonium salt-based ionic liquids (B) such as trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)imide, triethylpentylphosphonium bis(trifluoromethylsulfonyl)imide, triethyloctylphosphonium bis(trifluoromethylsulfonyl)imide, tri-n-butylmethylphosphonium bis(trifluoromethylsulfonyl)imide, and tetrabutylphosphonium tetraphenylborate; ammonium salt-based ionic liquids such as tributylmethylammonium bis(trifluoromethylsulfonyl)imide (FC-4400, 3M Japan); pyridinium salt-based ionic liquids such as N-butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide (CIL-312, Nippon Carlit Co., Ltd.); imidazolium salt-based ionic liquids; and pyrrolidinium salt-based ionic liquids.
[0054] The plasticizer may be arbitrarily selected from known plasticizers such as polyethylene glycol, polyamide oligomer, ethylene bisstearamide, phthalate ester, adipic acid ester, polystyrene oligomer, polyethylene wax, silicone oil, and mineral oil.
[0055] The release agent can be arbitrarily selected from known agents such as polyethylene wax, silicone oil, stearyl phosphite, long-chain carboxylic acid, metal salt of long-chain carboxylic acid, and higher fatty acid ester of monohydric or polyhydric alcohol.
[0056] The flame retardant can be arbitrarily selected from known flame retardants such as phosphorus-based flame retardants such as bisphenol A bis(diphenyl phosphite), tricresyl phosphate, triphenyl phosphate, and tris-3-chloropropyl phosphate; bromine-based flame retardants such as 2,2-bis[4-(3,3-dibromopropoxyl)-3,5-dibromophenyl]propane, bis(3,5-dibromo-4-dibromopropyloxyphenyl)sulfone, ethylene bispentabromobenzene, and hexabromocyclododecane; silicone-based flame retardants; and hydroxide-based flame retardants such as magnesium hydroxide and aluminum hydroxide.
[0057] The flame retardant auxiliary may be selected from antimony compounds such as antimony trioxide and others.
[0058] <Method for producing polycarbonate resin composition> The method for producing the polycarbonate resin composition of the present disclosure is not particularly limited, and known methods for producing polycarbonate resin compositions can be widely adopted. For example, polycarbonate resin (A), phosphonium salt-based ionic liquid (B) and composite nanofiber (C), as well as additives to be blended as necessary, are mixed and kneaded. As a kneading method, for example, any physical blend such as melt kneading, solvent cast blending, latex blending, and polymer complex can be used, but the melt kneading method is preferred. The temperature of the melt kneading is not particularly limited, but is usually in the range of 240 to 320 ° C.
[0059] The kneading apparatus may be, for example, a tumbler, a Henschel mixer, a rotary mixer, a super mixer, a ribbon tumbler, a V blender, etc., and the mixed components are uniformly dispersed by the kneading method, then melt-kneaded and pelletized. A single-screw or multi-screw extruder is generally used for melt-kneading and pelletization, but a Banbury mixer, a roller, a co-kneader, a blast mill, a Prabender blastograph, etc. may also be used, and these are operated batchwise or continuously.
[0060] Alternatively, instead of melt-kneading, the resin pellets, the hydrolysis resistance improver, and other additives may be mixed together, and the mixed components may be used as a molding resin, which is then melt-kneaded in the heating barrel of a molding machine, a method known as mold blending.
[0061] Embodiment 2 The molded article according to the present embodiment is made of the above-mentioned polycarbonate resin composition. Since the molded article according to the present embodiment is made of the above-mentioned polycarbonate resin composition, it has an effect of ensuring transparency and being less susceptible to both hydrophilic dust stains and hydrophobic dust stains.
[0062] The molded article of the present embodiment can be produced by melt-kneading the polycarbonate resin composition containing the above-mentioned polycarbonate resin (A), phosphonium salt-based ionic liquid (B) and composite nanofibers (C), pelletizing the mixture, and molding the mixture by various molding methods. Alternatively, the molded article can be produced by directly molding the resin melt-kneaded in an extruder without going through pelletization.
[0063] The shape of the molded product is not particularly limited, but can be appropriately selected according to the use and purpose of the molded product. For example, plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, porous, foamed, polygonal, irregular, hollow, frame-like, box-like, panel-like, etc. can be mentioned. Specifically, various shapes such as automobile interior panels, automobile (two-wheeled vehicle) headlamp lenses, windows, housings, etc., and special shapes can be mentioned. In addition, the molded product may have a concave-convex shape transferred to its surface, or may have a three-dimensional shape having a three-dimensional curved surface. Furthermore, when used as a sheet, film, plate-like, etc., it may be a multilayer structure laminated with other resin sheets.
[0064] The molding method is not particularly limited, and any conventionally known molding method can be used, including injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, inflation molding, etc. Furthermore, surface treatments such as corona discharge treatment, flame treatment, plasma treatment, ozone treatment, etc. that are usually used industrially can also be applied.
[0065] (Total light transmittance) The molded article of this embodiment has excellent transparency even at a thickness of about 0.5 to 6.0 mm, and the total light transmittance of a molded article having a thickness of 2.0 mm is 86% or more, and preferably 88% or more.
[0066] Here, total light transmittance refers to all light that is transmitted when light equivalent to a D65 light source is incident on the measurement object, and the D65 light source refers to light that reproduces an outdoor lighting environment. The state without a test piece is taken as 100%, and the closer the value is to 100%, the more transparent it is.
[0067] The total light transmittance can be measured, for example, according to a measurement method conforming to JIS K7361-1:1997 "Plastics - Test method for total light transmittance of transparent materials - Part 1: Single beam method" using a molded product with a thickness of 2.0 mm and an ultraviolet-visible-near infrared (UV-Vis-NIR) spectrophotometer (Shimadzu Corporation, Solid Spec-3700 DUV) at a temperature of 23°C.
[0068] (Haze) In the molded article of the present embodiment, the haze of a molded article having a thickness of 2.0 mm is 7% or less, and preferably 6% or less.
[0069] Here, haze refers to the degree of light scattering, which can cause a material to become opaque even if it does not absorb light. The lower the value, the more transparent the material is.
[0070] Haze can be measured, for example, according to a measurement method conforming to JIS K7136:2000 "Determination of haze of plastics - transparent materials" using a molded product with a thickness of 2.0 mm and a haze meter (NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.) at a temperature of 23°C under a D65 light source.
[0071] Moreover, the haze can be calculated by the following formula (1). Haze (%) = Diffused light component / Total light transmittance × 100 Formula (1) The light contained in the total light transmittance includes a parallel light component and a diffuse light component, and the haze is a numerical representation of the proportion of the diffuse light component in the total light transmittance. EXAMPLES
[0072] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to these examples.
[0073] <Evaluation method> The evaluation was performed by the following method. The test specimens used in the following evaluations were flat test specimens (100 mm length × 100 mm width × 2.0 mm thickness), and were evaluated after being left for one week in an environment of 23°C temperature and 50% humidity.
[0074] (1) Transparency (total light transmittance) The flat test pieces were measured at 23°C using an ultraviolet-visible-near infrared (UV-Vis-NIR) spectrophotometer (Shimadzu Solid Spec-3700 DUV) in accordance with JIS K7361-1:1997 "Plastics - Test method for total light transmittance of transparent materials - Part 1: Single beam method." A total light transmittance of 86% or more was considered good.
[0075] (2) Transparency (haze) Using the measurement method based on JIS K7136:2000 "Determination of haze for plastics - transparent materials", the above flat test pieces were measured with a haze meter (NDH2000 manufactured by Nippon Denshoku Industries Co., Ltd.) under a D65 light source at a temperature of 23° C. A haze of 7% or less was considered good.
[0076] (3) Antistatic properties (surface resistivity) The flat test piece was used to measure the resistivity under the following test conditions using a resistivity meter (Hiresta UP MCP-HT450, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). The smaller the value, the better the antistatic property. 12 "A" is when the surface resistivity is less than 10 Ω / sq. 12 Cases of Ω / sq or more were rated "B". [Test conditions] Voltage: 1000V Time: 60 seconds Temperature: 23℃ Humidity: 50%
[0077] (4) Dust adhesion Powders that conform to JIS Z8901:2006 "Test Powders and Test Particles" were used. Kanto loam (JIS test powder 1 type 11) was used for evaluating hydrophilic dust adhesion, and carbon black (JIS test powder 1 type 12) was used for evaluating hydrophobic dust adhesion. Dust adhesion was evaluated by blowing a certain amount (5g) of dust onto the surface of the molded product with air, observing the surface of the molded product at 100x magnification using a digital microscope (Keyence Corp. VHX-5000), and determining the dust adhesion rate (dust-adhered area ratio) through image processing. A dust adhesion rate of less than 4% was given an "A," and a dust adhesion rate of 4% or more was given a "B."
[0078] (5) Overall Judgment Total light transmittance is 86% or more, haze is 7% or less, and surface resistivity is 10 12 The case where the surface roughness is less than Ω / sq and the hydrophilic and hydrophobic dust adhesion rate is less than 4% is indicated as "A", and the case where even one of the above items is not met is indicated as "B".
[0079] <Examples 1 to 10 and Comparative Examples 1 to 11> The components shown in Tables 1 and 2 were mixed in the composition ratios shown in Tables 1 and 2, and melt-kneaded at 280° C. using a twin-screw kneading extruder (TEX-26SX, manufactured by Shibaura Electric Industries, Ltd.) to prepare 3-5 mm pellets of a polycarbonate resin composition.
[0080] The obtained pellets were molded into flat test pieces (length 100 mm × width 100 mm × thickness 2 mm) for evaluation (Examples 1 to 10, Comparative Examples 1 to 11) using an electric injection molding machine (NEX110IV-9EG manufactured by Nissei Plastic Industrial Co., Ltd.) The basic conditions for injection molding were a resin temperature of 280°C and a mold temperature of 80°C.
[0081] The components shown in Tables 1 and 2 (each component represented by a symbol) are as follows.
[0082] [Polycarbonate resin: component A] A-1: Iupilon HL3503 manufactured by Mitsubishi Engineering Plastics Corporation A-2: Toughlon LC1500 manufactured by Idemitsu Kosan Co., Ltd. A-3: SD Polycarbonate 303-30 manufactured by Sumika Polycarbonate Co., Ltd. A-4: Teijin Ltd. Panlite L-1225ZL A-5: Iupilon HL3003 manufactured by Mitsubishi Engineering Plastics Corporation A-6: Iupilon SGH1010A (glass fiber 10 parts by weight) manufactured by Mitsubishi Engineering Plastics Corporation
[0083] [Phosphonium salt-based ionic liquid: Component B] (B-1) Tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-2) Tetrabutylphosphonium dodecylbenzenesulfonate (Elecut S-418, manufactured by Takemoto Oil Co., Ltd.) (B-3) Tributyldodecylphosphonium bromide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-4) Tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide [IL-AP3, manufactured by Koei Chemical Industry Co., Ltd.]
[0084] [Ammonium salt-based ionic liquid, pyridinium salt-based ionic liquid: component B'] (B'-1) Tributylmethylammonium bis(trifluoromethylsulfonyl)imide [3M Japan Ltd. FC-4400] (B'-2) N-Butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide [Nippon Carlit Co., Ltd. CIL-312]
[0085] [Composite nanofiber: component C] (C-1) Nanofibers made of alumina and silica (R30SP-H1, manufactured by Admatechs Co., Ltd.) (average fiber diameter: 2-50 nm, refractive index: 1.60) (C-2) Nanofibers made of alumina and silica (R30SP-M2, manufactured by Admatechs Co., Ltd.) (average fiber diameter: 2-50 nm, refractive index: 1.58)
[0086] [Metal oxide: component C'] (C'-1) Antimony-doped tin oxide (ATO) [FS-10P, manufactured by Ishihara Sangyo Kaisha, Ltd.] (average fiber diameter: 10-20 nm, refractive index: 2.0-2.2)
[0087] Tables 1 and 2 show the above evaluation results (1) to (4) and (5) overall judgment for the obtained flat test pieces for evaluation (Examples 1 to 10 and Comparative Examples 1 to 11).
[0088] [Table 1]
[0089] [Table 2]
[0090] From the evaluation results shown in Table 1, it can be confirmed that in the examples, which are molded articles made of polycarbonate resin compositions satisfying the configuration requirements of the present disclosure, polycarbonate resin compositions having excellent transparency and an anti-fouling effect in that both hydrophilic and hydrophobic dust stains are difficult to adhere to can be obtained.
[0091] On the other hand, Comparative Example 1 did not contain components B and C, and therefore was poor in antistatic properties and dust adhesion. Comparative Example 2 contained component B but did not contain component C, and therefore had improved transparency and hydrophilic dust adhesion, but was poor in antistatic properties and hydrophobic dust adhesion. Comparative Example 5 contained component C but did not contain component B, and therefore was poor in antistatic properties and dust adhesion, similar to Comparative Example 1. From these results, it can be confirmed that the inclusion of all of components A to C is a necessary constituent requirement in the present disclosure.
[0092] In addition, although Comparative Examples 7 to 10 contained all of the components A to C, the content of the component C in Comparative Example 7 and the content of the component B in Comparative Example 9 were higher than the specified amounts, so that the antistatic properties and dust adhesion were improved but the transparency was poor. In addition, the content of the component C in Comparative Example 8 and the content of the component B in Comparative Example 10 were lower than the specified amounts, so that the transparency was improved but the antistatic properties and dust adhesion were poor. From these results, it can be confirmed that the inclusion of all of the components A to C and the respective specified amounts are necessary constituent elements of the present disclosure.
[0093] Furthermore, Comparative Example 3 contained an ammonium salt-based ionic liquid (B'-1) instead of component B, and Comparative Example 4 contained a pyridinium salt-based ionic liquid (B'-2) instead of component B, and therefore had poor antistatic properties and hydrophobic dust adhesion. These results confirm that a phosphonium salt-based ionic liquid (component B) is the optimal ionic liquid.
[0094] In addition, Comparative Example 6 contained antimony-doped tin oxide (C'-1) instead of component C, and therefore was inferior in transparency, antistatic properties, and hydrophobic dust adhesion rate. In addition, Comparative Example 11 contained glass fiber (A-6) instead of component C, and therefore was inferior in antistatic properties and dust adhesion rate. From these results, it can be confirmed that composite nanofiber is optimal as component C.
[0095] Although not shown in Tables 1 and 2, when the mechanical properties (tensile strength, tensile elongation at break, and Charpy impact strength) were evaluated in Example 1 and Comparative Example 1, equivalent evaluation results were obtained, and it was confirmed that no deterioration in the mechanical properties was observed even when components B to C were blended with component A.
[0096] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.
Claims
1. Contains 100 parts by weight of polycarbonate resin, 0.5 to 5.0 parts by weight of phosphonium salt-based ionic liquid, and 0.01 to 0.09 parts by weight of composite nanofibers; The composite nanofiber is made by combining two or more metal oxides, The metal oxides include alumina and silica; The composite nanofiber has an average fiber diameter of 100 nm or less, The composite nanofiber is a polycarbonate resin composition having a refractive index of 1.50 to 1.80 at a wavelength of 589.3 nm of sodium D line.
2. 2. The polycarbonate resin composition according to claim 1, wherein the phosphonium salt-based ionic liquid comprises at least one selected from the group consisting of tributyldodecylphosphonium bis(trifluoromethanesulfonyl)imide, tributyldodecylphosphonium bromide, and tetrabutylphosphonium dodecylbenzenesulfonate.
3. The polycarbonate resin composition according to claim 1 or 2, wherein the composite nanofiber is a composite of alumina and silica.
4. A molded article comprising the polycarbonate resin composition according to any one of claims 1 to 3.
5. A method for producing the polycarbonate resin composition according to any one of claims 1 to 3, comprising the steps of: A method for producing a polycarbonate resin composition, comprising melt-kneading a polycarbonate resin, a phosphonium salt-based ionic liquid, and composite nanofibers.
Citation Information
Patent Citations
JP1973070256A
Lithium ion battery
JP2005285605A
Method for manufacturing of antistatic polycarbonate resin molded article, and molded article
JP2009107286A
Antistatic polycarbonate resin composition
JP2011057757A
Method of producing inorganic composite nanofiber
JP2014173214A